PENGARUH PEMANFAATAN MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR SISWA PADA BIDANG STUDI IPA KELAS VII DI SMPN 13 MAKASSAR - ulya, Andi fahrullah; H, Nurhikmah; Febriati, Farida (Indonesian Journal of Educational Technology, 2024)
This quantitative study examines the impact of Ispring Suite media on student learning outcomes. Data collection was carried out using test sheets and questionnaires. Reliability tests were performed to calculate the average score for each question item related to Ispring Suite media and its effect on the learning outcomes of Grade VII students at SMPN 13 Makassar. After completing the reliability tests, the data underwent a normality test, which revealed that the data was not normally distributed, likely due to the small sample size. As a result, a non-parametric test, specifically the Wilcoxon test, was used to analyze the data. The Wilcoxon test results showed a significant Asymp value of 0.005, which is less than the 0.05 significance level. According to the decision criteria for the Wilcoxon test, when the Asymp Sig. value is below 0.05, H0 is rejected, and Ha is accepted. Therefore, based on these findings, it can be concluded that the use of Ispring Suite media has a significant effect on student learning outcomes in Grade VII science subjects at SMPN 13 Makassar.